SPECIAL FEATURES OF INTERACTIONS OF MAGNETIC PROPERTIES OF CAST IRON WITH THEIR STRUCTURE AND MAGNETIC CONTROL METHODS OF STRUCTURE OF PIG-IRON CASTINGS (review) - S. G. Sandomirskij (Литьë и металлургия)
Differences of magnetic properties of cast iron with various structure and tasks of structure control of castings by their magnetic parameter are analyzed in the article.